Use of infrared thermography for concrete strength assessment with different overlay - Mohammad Iskandar Halimie, Abd Halim (2017)
Concrete has been used in construction for more than a century now and have it advantages and disadvantages. A number of existing structures exhibit distresses and lack of load‐carrying capacity. Repair and strengthening of existing structures are in fact among the biggest challenges civil engineers will have to face in the years to come. Among different approaches that can be considered for concrete rehabilitation is bonded overlays because most economical alternative. Overlays are particularly suitable in the case of structures with large surface areas, where it can be either poured or sprayed. The primary purpose of overlays is to extend the life of the candidate concrete structures, either by restoring a smooth sound surface and improving the load‐carrying capacity by a thickness increase. The objective of this research is to determine the strength of concrete with different overlay method using IRT and ultrasonic pulse velocity and to analyze the effectiveness of the IRT to detect the color changes produce by the beam with different grade. Infrared camera will capture image of two layers concrete and analyse the colour changes between two layers during flexural test. UPV will determine the quality and the connection between two layers concrete through the velocity readings. By using different concrete overlay method the UPV test able to detect the difference between two layer of the concrete where it show the increasing of the UPV reading along with the increasing of the concrete grade but not by using IRT. It is because the flexural machine is transmit higher temperature compare to the beam structure and IRT tend to detect the object with higher temperature. There are different colour produced by IRT image, where the object dominant in temperature produce brighter colour. The effectiveness of the IRT to detect the colour changes produce by the beam with different grade and to determine it strength cannot be achieved because IRT unable to produce colour changes on the beam. Therefore the IRT test is less effective compare to the UPV during the determination of concrete with different grade and also it strength.